The Quantization of a Kerr-AdS Black Hole. (5th February 2018) - Gerhardt, Claus
Abstract : We apply our model of quantum gravity to a Kerr-AdS space-time of dimension2 m + 1, m ≥ 2, where all rotational parameters are equal, resulting in a wave equation in a quantum space-time which has a sequence of solutions that can be expressed as a product of stationary and temporal eigenfunctions. The stationary eigenfunctions can be interpreted as radiation and the temporal ones as gravitational waves. The event horizon corresponds in the quantum model to a Cauchy hypersurface that can be crossed by causal curves in both directions such that the information paradox does not occur. We also prove that the Kerr-AdS space-time can be maximally extended by replacing in a generalized Boyer-Lindquist coordinate system ther variable byρ = r 2 such that the extended space-time has a timelike curvature singularity inρ = - a 2 .